2014
DOI: 10.1021/am405619v
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium(II) Bis(trifluoromethane sulfonyl) Imide-Based Electrolytes with Wide Electrochemical Windows for Rechargeable Magnesium Batteries

Abstract: We present a promising electrolyte candidate, Mg(TFSI)2 dissolved in glyme/diglyme, for future design of advanced magnesium (Mg) batteries. This electrolyte shows high anodic stability on an aluminum current collector and allows Mg stripping at the Mg electrode and Mg deposition on the stainless steel or the copper electrode. It is clearly shown that nondendritic and agglomerated Mg secondary particles composed of ca. 50 nm primary particles alleviating safety concern are formed in glyme/diglyme with 0.3 M Mg(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
470
3
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 418 publications
(498 citation statements)
references
References 30 publications
20
470
3
3
Order By: Relevance
“…These systems provide a relatively facile delivery of Mg 2+ ions in a chloride-free electrolyte and an 28,30,48,49 in cells with a working Mg electrode. However, these electrolytes suffer from low (≤87%) CE, significant overpotential, destructive incompatibilities with Mg metal resulting in passivation of the anode surface, and parasitic loss of electrolyte due to the electrochemical decomposition of solvent (e.g., AN) mimicking Mg-plating/insertion.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These systems provide a relatively facile delivery of Mg 2+ ions in a chloride-free electrolyte and an 28,30,48,49 in cells with a working Mg electrode. However, these electrolytes suffer from low (≤87%) CE, significant overpotential, destructive incompatibilities with Mg metal resulting in passivation of the anode surface, and parasitic loss of electrolyte due to the electrochemical decomposition of solvent (e.g., AN) mimicking Mg-plating/insertion.…”
Section: ■ Introductionmentioning
confidence: 99%
“…50 Another peculiarity of the Mg(TFSI) 2 /G2 electrolyte is the debated instability of plating/stripping overpotentials at different salt concentrations and current densities. 28,50,51 In pursuit of understanding the Mg(TFSI) 2 electrolyte behavior and its potential improvement, extensive computational studies were carried out. 5,6,27,31 Using a combination of classical MD simulations and quantum chemistry calculations hybridized with implicit solvent models, 52 it was shown that the solvent donor strength and its chelating ability largely determine the solubility of Mg(TFSI) 2 and the ion-pair solvation structure.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[70] The Mg/ CMK3-S cell exhibited a very low-discharge plateau of 0.2 V with a capacity of 500 mAh/g in the first discharge and the cell could be cycled only for several cycles. Itaoka et al prepared sulfur composites with S and bis(alkenyl) compound with a crown or linear ether unit.…”
Section: Conductive Salt-based Electrolytesmentioning
confidence: 96%
“…[70] However, this electrolyte shows a high overpotential (about 2 V) and a low cycling efficiency. Recently, Ma et al reported the enhancement of electrochemical properties of Mg(TFSI) 2 tetraglyme solution by adding some quantities of Mg(BH 4 ) 2 to scavenge water and suggested that removal of water from the electrolytes is vital to achieve reversible Mg cycling.…”
Section: Electrolytes From Chloride-free Magnesium Saltsmentioning
confidence: 99%
“…7,8 The observed cycling performance of a novel HMNB configuration, NaTi 2 (PO 4 ) 3 /C vs Mg (NaTi 2 (PO 4 ) 3 /C//Mg), indicates that 0.3 M Mg(TFSI) 2 + 0.5 M NaBF 4 in diglyme may be a promising electrolyte candidate for future HMNBs.…”
mentioning
confidence: 99%